(NtOMOGRAFIQ IONOSFERY (B/s - (NkUNICYN(B, (NwQ^ESLAW eWGENXEWI^s; (NtERE]ENKO(B, (NeWGENIJ dMITRIEWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 160-173 (227 (NNAZW(B.)s
Keywords: (NiONOSFERAs; (NtOMOGRAFIQs